Ornithological observations from Maratua and Bawean Islands, Indonesia - Ryan C. Burner; Subir B. Shakya; Tri Haryoko; M. Irham; Dewi M. Prawiradilaga; Frederick H. Sheldon (Treubia, 2018)
Indonesia’s many islands, large and small, make it an important center of avian diversity and endemism. Current biogeographic understanding, however, is limited by the lack of modern genetic samples for comparative analyses from most of these islands, and conservation efforts are hampered by the paucity of recent information from small islands peripheral to major, more commonly visited islands. In November and December 2016, we visited Maratua, an oceanic coral atoll 50 km east of Borneo, and Bawean, a volcanic island on the Sunda continental shelf 150 km north of Java, to survey birds and collect specimens for morphological and genetic analysis. We detected many of the birds on Maratua’s historical lists and added several new resident and migratory species. Notably, we did not detect the Maratua White-rumped Shama (Copsychus malabaricus barbouri). On Bawean, we found the forests to be nearly silent and detected remarkably few resident land-bird species overall. The severe population reduction of C. m. barbouri on Maratua and the drastic reduction of forest birds on Bawean probably result from overexploitation by the cage-bird trade in the first case and a combination of the cage-bird trade and pellet-gun hunting in the second.